Pengembangan Spot Play Ground sebagai Tempat Wisata Edukasi di Wisata Alam Sawung Padi Desa Wonokerso - Bachtiar, Muhammad Affan; Ali, Khoharudin; Aji, Miping Purmisanto; Aditya, Muhammad Alif; Ansyorie, Mohammad Musthofa Al (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2024)
Wonokerso Village is situated in the Pakisaji District of Malang Regency. The village boasts a sawung padi agro-tourism area, which serves as an educational tourism destination for the community. The village government and local farmers manage this agro-tourism site. The addition of a playground is expected to attract more tourists to Wonokerso Village. Taking a tour of the village can be a refreshing experience for those passing through. The development of Sawung Padi agro-tourism has resulted in the creation of a playground, which is a significant achievement for the village. Wonokerso Village is a heavily travelled industrial village. There are also plans to further develop Wonokerso Village into a tourist destination in the future. Additionally, the goals of this development project for the partner village include reporting, journal publications, intellectual property rights, and other related objectives. Desa Wonokerso terletak di Kecamatan Pakisaji, Kabupaten Malang. Desa ini memiliki kawasan agrowisata sawung padi yang menjadi tujuan wisata edukasi bagi masyarakat. Pemerintah desa dan petani setempat mengelola tempat agrowisata ini. Penambahan taman bermain diharapkan dapat menarik lebih banyak wisatawan ke Desa Wonokerso. Berkeliling desa dapat menjadi pengalaman yang menyegarkan bagi mereka yang melewatinya. Pengembangan agrowisata Sawung Padi telah menghasilkan taman bermain, yang merupakan pencapaian signifikan bagi desa. Desa Wonokerso merupakan desa industri yang ramai dikunjungi. Ada juga rencana untuk mengembangkan Desa Wonokerso lebih lanjut menjadi tujuan wisata di masa depan. Selain itu, tujuan dari proyek pengembangan ini untuk desa mitra meliputi pelaporan, publikasi jurnal, HKI, dan tujuan terkait lainnya.